Foreign Aid for Alliance: Indonesia’s Effort to Find Support in the South Pacific Region - Maria Indira Aryani; Renita Dwi Hapsari (JOSAR (Journal of Students Academic Research), 2021)
United Liberation Movement for West Papua (ULMWP) has been actively seeking for independence since its inception in 1969. ULMWP founding fathers, as well as leaders, stated that this movement aims at achieving West Papua independence and freedom, while at the same time, is being regarded in Indonesia as a separatist movement, representing only a small portion of Papuans abroad. In order to achieve this goal, the ULMWP has been trying to gain international recognition and support, mainly from its neighboring countries and region. One of ULMWP constant supporter is Vanuatu, who has been declaring its support for the ULMWP since the time of its first Prime Minister Walter Hadye Lini in 1980. Vanuatu often calls for Papuan Independence in various international arena, such as the UN Assemby and the Melanesian Spearhead Groups (MSG) High Commisioner Meetings. To ward off Vanuatu’s influence in the South Pacific region, Indonesia has been actively providing and offering aids for South Pacific countries, as a token of appreciation for their support for acknowledging Indonesia’s sovereignty. This paper thus aimed at answering and explaining how Indonesia is using foreign aid as a mean to build alliance in the South Pacific and in the MSG. Foreign aid almost always contains political interest, in this particular case, Indonesian aids to the South Pacific are aimed at maintaining relations and supports from the South Pacific countries for its sovereignty. As a result, prominent South Pacific countries have expressed their support for Indonesia’s sovereignty